PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MENGGUNAKAN MEDIA KARTU SUKU KATA DI SEKOLAH DASAR - Yeni Erita; Nofia Henita; Deni Okta Nadia (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Reading has a big effect on students' ability to accept subject matter, especially text-based learning, students who are unable to read well will have difficulty participating in learning activities for all subjects. This study aims to improve the process and skills of beginning reading through the use of syllable card media for first grade students at Public Elementary School 12 Pahambek. This type of research is Classroom Action Research (CAR). The subjects of this study were 10 students in class I at 12 Pahambek Public Elementary School. The object of research is the improvement of beginning reading skills. This research was conducted in two cycles with each cycle consisting of two meetings. Data collection techniques using observation and tests. Data analysis techniques using descriptive quantitative and qualitative descriptive analysis. The results of the study showed that early reading skills through the use of syllable card media in grade I students at SD Negeri 12 Pahambek experienced a good improvement. This is evident from the average achievement in the pre-action percentage of 37.48%, in cycle I increased to 54.66% and in cycle II to 84.19%. Thus the results of this second cycle have fulfilled the predetermined action success criteria.